An Overview of HDAC Inhibitors and their Synthetic Routes - Peng, Xiaopeng; Liao, Guochao; Sun, Pinghua; Yu, Zhiqiang; Chen, Jianjun (Current topics in medicinal chemistry, 2019)
Epigenetics play a key role in the origin, development and metastasis of cancer. Epigenetic processes include DNA methylation, histone acetylation, histone methylation, and histone phosphorylation, among which, histone acetylation is the most common one that plays important roles in the regulation of normal cellular processes, and is controlled by histone deacetylases (HDACs) and histone acetyltransferases (HATs). HDACs are involved in the regulation many key cellular processes, such as DNA damage repair, cell cycle control, autophagy, metabolism, senescence and chaperone function, and can lead to oncogene activation. As a result, HDACs are considered to be an excellent target for anti-cancer therapeutics like histone deacetylase inhibitors (HDACi) which have attracted much attention in the last decade. A wide-ranging knowledge of the role of HDACs in tumorigenesis, and of the action of HDACi, has been achieved. The primary purpose of this paper is to summarize recent HDAC inhibitors and the synthetic routes as well as to discuss the direction for the future development of new HDAC inhibitors.